2018
DOI: 10.1371/journal.pone.0196084
|View full text |Cite
|
Sign up to set email alerts
|

Biomonitoring of blood cholinesterases and acylpeptide hydrolase activities in rural inhabitants exposed to pesticides in the Coquimbo Region of Chile

Abstract: In Chile, agriculture is a relevant economic activity and is concomitant with the use of pesticides to improve the yields. Acute intoxications of agricultural workers occur with some frequency and they must be reported to the surveillance system of the Ministry of Health. However the impacts of chronic and environmental pesticide exposure have been less studied. Among pesticides frequently used in Chile for insects control are organophosphates (OP) and carbamates (CB). They are inhibitors of acetylcholinestera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 54 publications
(50 reference statements)
0
13
0
4
Order By: Relevance
“…However, these workers also are exposed to other factors such as pesticides and extreme temperatures. These exposures, along with vibration, may increase the risk of developing certain cancers, respiratory problems and neurodegenerative diseases (Suratman, Edwards,Babina 2015; Manyilizu et al 2016; Kachuri et al 2017; Bencko,Yan Li Foong 2017; Prado et al 2017; Piel et al 2017; Darcey et al 2018; Prudente et al 2018; Ramirez-Santana et al 2018; Anderson et al 2018). Studies need to be performed to determine how exposure to these various factors affect the risk of developing these vibration-induced illnesses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these workers also are exposed to other factors such as pesticides and extreme temperatures. These exposures, along with vibration, may increase the risk of developing certain cancers, respiratory problems and neurodegenerative diseases (Suratman, Edwards,Babina 2015; Manyilizu et al 2016; Kachuri et al 2017; Bencko,Yan Li Foong 2017; Prado et al 2017; Piel et al 2017; Darcey et al 2018; Prudente et al 2018; Ramirez-Santana et al 2018; Anderson et al 2018). Studies need to be performed to determine how exposure to these various factors affect the risk of developing these vibration-induced illnesses.…”
Section: Introductionmentioning
confidence: 99%
“…Agricultural workers can be exposed to vibration and various pesticides. Pesticide exposure has been associated with the development of peripheral neuropathies, neurodegenerative disorders, and reproductive problems in workers (Suratman, Edwards,Babina 2015; Iavicoli et al 2017; Kab, Moisan,Elbaz 2017; Prudente et al 2018; Ramirez-Santana et al 2018; Anderson et al 2018). Understanding how these various exposures may contribute to the development of health problems is important determining the best actions to take to reduce exposure and the incidence of injury and disease.…”
Section: Introductionmentioning
confidence: 99%
“…However, we currently do not have an explanation of why we only found a reduction in the hemoglobin of exposed males, but not in exposed females. A decrease in AChE activity was observed in several studies after OP exposure [ 8 , 40 , 41 , 42 ]. In this study, the mean value of AChE enzymatic activity, the specific activity for the exposed participants was lower than the enzymatic activity of the nonexposed participants.…”
Section: Discussionmentioning
confidence: 94%
“…In this study, the mean value of AChE enzymatic activity, the specific activity for the exposed participants was lower than the enzymatic activity of the nonexposed participants. The decrease in AChE activity was thought to be related to the duration and frequency of pesticide exposure [ 42 ]. In this study, a relationship was found between AChE activity and the span of the exposure, using the number of years working in the field (~3 years average).…”
Section: Discussionmentioning
confidence: 99%
“…Another reason for the presence of similar abnormal SChE in spraying and non-spraying workers might be due to environmental pesticide exposure in their residences due to the drift of pesticides from both open field and greenhouse farms. We have no information about the overall environmental exposure, but in support of this argument, a study conducted in Chile and Thailand found no significant difference in cholinesterase levels among study participants who were occupationally exposed and those who were environmentally exposed [41,42].…”
Section: Discussionmentioning
confidence: 96%